2018
DOI: 10.1007/978-1-4939-7295-1_17
|View full text |Cite
|
Sign up to set email alerts
|

Design, Engineering, and Characterization of Prokaryotic Ligand-Binding Transcriptional Activators as Biosensors in Yeast

Abstract: In cell factory development, screening procedures, often relying on low-throughput analytical methods, are lagging far behind diversity generation methods. This renders the identification and selection of the best cell factory designs tiresome and costly, conclusively hindering the manufacturing process. In the yeast Saccharomyces cerevisiae, implementation of allosterically regulated transcription factors from prokaryotes as metabolite biosensors has proven a valuable strategy to alleviate this screening bott… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Stable S. cerevisiae strains were routinely cultivated at 30 °C on YPD (1% (w/v) yeast extract, 2% (w/v) peptone 2% (w/v) dextrose, solidified with 2% (w/v) agar) medium, whereas plasmid-containing strains or libraries were cultivated in synthetic complete medium lacking leucine (SC-Leu; 6.7 g/L yeast nitrogen base without amino acids, 1.62 g/L yeast synthetic drop-out medium supplement without leucine (Y1376, Sigma-Aldrich), 2% (w/v) dextrose, pH 5.6, 2% (w/v) agar in case of plates). Mineral medium supplemented with tryptophan (7.5 g/L (NH 4 ) 2 SO 4 , 14.4 g/L KH 2 PO 4 , 0.5 g/L MgSO 4 •7H 2 O, 2 g/L dextrose, trace metals, vitamins, 0.02 g/L tryptophan, pH 4.5) was freshly prepared as described previously 58 , and medium was handled as outlined by Ambri et al 59 . Diacids, cis, cis -muconic acid (Sigma, CAS Number 1119-72-8, Product Number: 15992) or adipic acid (TCI, CAS Number:124-04-9 Product Number: A0161), were dissolved freshly to the medium on the day of handling, after which the pH was adjusted to 4.5 and the solution filter-sterilized as previously described 59 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stable S. cerevisiae strains were routinely cultivated at 30 °C on YPD (1% (w/v) yeast extract, 2% (w/v) peptone 2% (w/v) dextrose, solidified with 2% (w/v) agar) medium, whereas plasmid-containing strains or libraries were cultivated in synthetic complete medium lacking leucine (SC-Leu; 6.7 g/L yeast nitrogen base without amino acids, 1.62 g/L yeast synthetic drop-out medium supplement without leucine (Y1376, Sigma-Aldrich), 2% (w/v) dextrose, pH 5.6, 2% (w/v) agar in case of plates). Mineral medium supplemented with tryptophan (7.5 g/L (NH 4 ) 2 SO 4 , 14.4 g/L KH 2 PO 4 , 0.5 g/L MgSO 4 •7H 2 O, 2 g/L dextrose, trace metals, vitamins, 0.02 g/L tryptophan, pH 4.5) was freshly prepared as described previously 58 , and medium was handled as outlined by Ambri et al 59 . Diacids, cis, cis -muconic acid (Sigma, CAS Number 1119-72-8, Product Number: 15992) or adipic acid (TCI, CAS Number:124-04-9 Product Number: A0161), were dissolved freshly to the medium on the day of handling, after which the pH was adjusted to 4.5 and the solution filter-sterilized as previously described 59 .…”
Section: Methodsmentioning
confidence: 99%
“…Mineral medium supplemented with tryptophan (7.5 g/L (NH 4 ) 2 SO 4 , 14.4 g/L KH 2 PO 4 , 0.5 g/L MgSO 4 •7H 2 O, 2 g/L dextrose, trace metals, vitamins, 0.02 g/L tryptophan, pH 4.5) was freshly prepared as described previously 58 , and medium was handled as outlined by Ambri et al 59 . Diacids, cis, cis -muconic acid (Sigma, CAS Number 1119-72-8, Product Number: 15992) or adipic acid (TCI, CAS Number:124-04-9 Product Number: A0161), were dissolved freshly to the medium on the day of handling, after which the pH was adjusted to 4.5 and the solution filter-sterilized as previously described 59 .…”
Section: Methodsmentioning
confidence: 99%
“…The design of such biosensors relies on systematic engineering and can use small-molecule binding transcriptional activators of various origins including prokaryotic. This was notably demonstrated by Skjoedt et al, who showed that several activators from different bacterial species are indeed able to function as allosterically regulated transcription factors in S. cerevisiae, thus creating a biosensor resource useful for future biotechnological [80,81]. Following this demonstration, they further developed a synthetic selection system that couples the concentration of muconic acid (a plastic precursor) to cellular fitness using the prokaryotic transcriptional regulator BenM upstream of the Kan r antibiotic resistance gene [82].…”
Section: Metabolic Biosensorsmentioning
confidence: 98%
“…Recent development in metabolite-responsive transcriptional factor (MRTF) based biosensors have expanded our ability to reprogram gene expression or control metabolic activity [19][20][21][22]. Most of these biosensors are developed in bacterial system.…”
Section: Introductionmentioning
confidence: 99%